How hard is it to maximize profit? Evidence from a 19th-century Italian state monopoly. (3rd January 2020) - Ciccarelli, Carlo; De Fraja, Gianni; Tiezzi, Silvia
Abstract: In this paper, we study the ability of the 19th-century Italian government to choose profit maximizing prices for a multiproduct monopolist. We use very detailed historical data on the tobacco consumption in 62 Italian provinces from 1871 to 1888 to estimate a differentiated product demand system. The demand conditions and the legal environment of the period made this market as close to a textbook monopoly as is practically possible. The government's stated aim for this industry was profit maximization: since at the time profits from tobacco were close to 10% of the revenues for the cash-strapped government, the stated aim was very likely the true one. Our empirical application uses historical price and cost data, and suggests that the government was not wide off the mark: the tobacco prices were 'not far' from those dictated by the multiproduct monopoly formulae for profit maximization with interdependent demand functions.